2011
DOI: 10.2105/ajph.2010.197285
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Exposure to Violence and Transphobia, and Correlates of Depression Among Male-to-Female Transgender Women With a History of Sex Work

Abstract: For THSW, psychological vulnerability must be addressed in counseling, support groups, and health promotion programs specifically tailored to race/ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
316
3
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(349 citation statements)
references
References 37 publications
22
316
3
8
Order By: Relevance
“…Notably, FTM participants were significantly more likely to report experiences of victimization and lifetime SI than MTF participants. Given that previous studies have relied heavily on convenience samples of higher-risk participants recruited primarily from urban locations, 6 our results may provide a more valid representation of the frequency and impact of discrimination and victimization experiences, given our geographically diverse, statewide sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, FTM participants were significantly more likely to report experiences of victimization and lifetime SI than MTF participants. Given that previous studies have relied heavily on convenience samples of higher-risk participants recruited primarily from urban locations, 6 our results may provide a more valid representation of the frequency and impact of discrimination and victimization experiences, given our geographically diverse, statewide sample.…”
Section: Discussionmentioning
confidence: 99%
“…1 Subsequently, published trans studies are often biased by the frequent recruitment of urban dwelling, socioeconomically disadvantaged, behaviorally risky individuals (i.e., through sex work). 6 Depression and anxiety are associated with experiences of discrimination and victimization, with these cited as prevalent mental health problems in trans samples (e.g., clinically significant depression estimated at 36.2%; clinically significant anxiety estimated at 40%). 7,8 Of further concern, lifetime prevalence estimates of suicidal ideation (SI) are as high as 60% in community-based samples of trans individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Social messaging and societal cisgendered expectations have been linked to transgender individuals adopting negative self-conceptions and having their connections to community and sense of belonging compromised (Chernicoff, 2002;Gagne et al, 1997). In one study, a third of African American MtF youth reported hearing "almost daily" that transgender persons were abnormal (Nemoto et al, 2011). Given the rigidity of masculine hegemony, and the perceived relinquishing of social power associated with transitioning from male to female, MtF transition is thought to be particularly challenging and socially stigmatized (Melendez & Pinto, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the transitioning goals, there are undoubtedly implications for transgender communities regarding the degree to which these communities are or are not seen by members as transitional and, moreover, the degree to which individuals desire to be out as trans or to "pass" as cisgendered (Schilt & Wiswall, 2008). In one study of 573 transgender women in Oakland and San Francisco, California, African American transgender women had the highest rate of hiding their transgender identity compared to all other races represented in the study (Nemoto et al, 2011). Gender identity development, transitioning, and coming out (or disclosure) often occurs in the context of stress, marginalization, and alienation.…”
Section: Transgender Identity and Minority Stressmentioning
confidence: 99%
“…3,4 A robust body of transgender research provides consistent evidence of mental health problems, including low self-esteem, 5,6 depression, [6][7][8][9][10][11][12] anxiety, 8,13,14 and suicidal ideation and suicide attempts. 4,10,15,16 In a sample of 226 transgender women, nearly half met criteria markers for depression and anxiety (51.4% and 40.4% respectively). 8 A systematic review of research with transgender individuals found that male-to-female (MTF) transgender individuals reported high rates of both suicidal ideation (weighted mean, 53.8%) and lifetime suicide attempts (weighted mean, 31.4%).…”
mentioning
confidence: 99%